NOS Inhibition-Induced Hypertension: Comparision of Stable and Gradual Dose of L-NNA Administration in Rats - Oktar, Süleyman; Yılmaz, Engin; Şahna, Engin; Aksulu, Hakkı Engin (Fırat University, 2007)
Objective: Chronic NOS inhibition-induced hypertension model is used commonly in essential hypertension researches. All these studies investigated using a stable doses of NOS inhibitor agents over experimental progress. But, it is decreased gradually synthesis and/or release of NO in essential hypertension. To better mimic essential hypertension, the doses of L-NNA (a NOS inhibitor) was administrated gradually increasing and was compared group of stable dose. Material and Method: Wistar rats were divided into 3 groups. Control group was done any administration. Second group took the stable concentration of L-NNA over 3 weeks and third group took gradually increasing concentration of L-NNA for 3 weeks. Blood pressure and heart rate are measured by tail-cuff method. Plasma nitrite/nitrate levels and kidney/body weigth ratios were also compared. Results: In the stable dose administrated group, heart rates decreased while the blood pressure increased. On the other hand, in the gradually increasing doses of L-NNA administrated group, heart rates did not change despite the increasing blood pressure. Plasma nitrite/nitrate levels decreased significantly but there was any change in kidney/body weight indexes in groups. Conclusion: It is suggested that is associated more gradually NOS inhibition than stable NOS inhibition with essential hypertension. ©2007, Fırat Uiversity, Medical Faculty

Amaç: Esansiyel hipertansiyon araştırmalarında yoğun olarak kullanılan kronik NOS inhibisyonu aracılı hipertansiyonda, bugüne kadar NOS inhibitörü ajanlar deney boyunca sabit dozlarda kullanılmıştır. Oysa esansiyel hipertansiyonda NO sentez ve/veya salıverilmesi progresif olarak azalmaktadır. Esansiyel hipertansiyonu daha iyi taklit etmek için bir NOS inhibitörü olan L-NNA giderek artan dozlarda uygulandı ve kan basıncı gelişimine etkileri sabit doz L-NNA uygulamasıyla karşılaştırıldı. Gereç ve Yöntem: Wistar sıçanlar 3 gruba ayrıldı: Kontrol grubuna deney süresince hiçbir uygulama yapılmadı. İkinci gruba L-NNA dozu sabit ve üçüncü gruba ise her hafta kademeli bir şekilde arttırılarak 3 hafta boyunca uygulandı. Kan basıncı ve kalp hızları tail-cuff metodu ile ölçüldü. Ayrıca, plazma nitrit/nitrat seviyeleri ve böbrek/vücut ağırlığı indeksleri karşılaştırıldı. Bulgular: Sabit doz L-NNA alan grubun kan basıncı artarken kalp hızının düştüğü, fakat L-NNA dozu kademeli olarak uygulandığında kan basıncı yükselmesine rağmen kalp hızında bir düşme olmadığı tespit edildi. Her iki grubun plazma nitrit/nitrat seviyeleri anlamlı düşerken böbrek/vücut ağırlığı indekslerinde bir değişiklik tespit edilmedi. Sonuç: NOS inhibisyonunun kademeli olarak artırılmasıyla kan basıncı artmasına rağmen kalp hızının değişmemesi, bu modelin sabit doz NOS inhibisyonuna göre esansiyel hipertansiyonla daha ilişki olabileceğine işaret etmektedir. ©2007, Fırat Üniversitesi, Tıp Fakültesi
NOS İnhibisyonu Aracılı Hipertansiyon: Sıçanlarda Sabit ve Kademeli doz L-NNA Uygulamalarının Karşılaştırılması